Reaching all writers: a pedagogical guide for evolving college writing classrooms - Giordano, Joanne Baird, author; Hassel, Holly, author; Heinert, Jennifer, author; Phillips, Cassandra, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Describes effective teaching practices to help all college writing instructors, regardless of their institutional contexts, make changes to teaching that support equitable and inclusive learning opportunities for students.--Provided by publisher.
Introduction: pedagogical adaptability -- Practices for teaching effective and equitable writing courses -- Thinking like a writer: translating threshold concepts in Writing Studies to the classroom -- Writing can be taught and learned -- Writers write for different purposes and audiences, and often in genres with predictable conventions -- Writing processes are individualized, require readers, and require revision -- Reading and writing are interconnected activities -- Writers make choices about language within cultural and social situations -- Conclusion: continuing to develop as a college writing teacher.
Keywords: Report writing -- Handbooks, manuals, etc.; Report writing -- Study and teaching (Higher); Academic writing -- Handbooks, manuals, etc.; Academic writing -- Study and teaching (Higher); English language -- Rhetoric -- Study and teaching (Higher); Writing centers